Seeing Race in Modern America - Guterl, Matthew Pratt, 1970- (Book collections on Project MUSE., 2013)
This book focuses on how and why we come to see race in very particular ways. What does it mean to see someone as a color? As racially mixed or ethnically ambiguous? What history makes such things possible? Drawing creatively from advertisements, YouTube videos, and everything in between, the author redirects our understanding of racial sight away from the dominant categories of color - away from brown and yellow and black and white - and instead insists that we confront the visual practices that make those same categories seem so irrefutably important. --